VD_FINDINFO 32/2010/JCL vom 19. Februar 2010 - VD Tribunal cantonal (2010)
ACTION EN LIBÉRATION DE DETTE, COMPTE COURANT, INTÉRÊTS COMPOSÉS, ACOMPTE, IMPUTATION | 116 CO, 17 CO, 69 al. 2 CO, 85 al. 1 CO, 83 al. 2 LP, 83 al. 3 LP